Priced Out : Do Adolescents from Low-Income Families Respond More to Cost-Sharing in Primary Care? - Haaga Tapio; Böckerman Petri; Kortelainen Mika; Tukiainen Janne (Walter de Gruyter GmbH, 2026)
We examine the heterogeneous effects of 14-21 euro copayments on primary care general practitioners (GPs) visits in Finland. Our study focuses on a triage-based appointment system in public primary care. Using an age-based regression discontinuity (RD) design and leveraging variation across Finnish municipalities in whether the copayment is charged, we analyze the effects at the 18th birthday, when previously exempted adolescents become subject to copayments. Using nationwide administrative data from 2011-2019, we find that GP visits decrease in the copayment municipalities by 4-5%. The reductions are largest for the bottom 20% of the equivalized family disposable income distribution: their GP use decreases by 0.08-0.10 annualized visits (7-10%). Unexpectedly, the effects are also larger than average (albeit rather temporary) for the top 50%, showing reductions of 6-8%. Compared to earlier studies focusing on moderate copayments and different populations, our effect estimates are smaller, and the heterogeneity by income level is weaker.